ChemInform Abstract: Structure and Magnetism in Hexagonal Tungsten Bronze Metal Oxides AM1/3W8/3O9 (A—K, Rb, Cs; M—Cr, Fe). Issue 13 (March 2015) - Ivanov, S. A; Sahu, J. R.; Voronkova, V. I.; Mathieu, R.; Nordblad, P.
Abstract Phase‐pure AM1/3W8/3O9 (A: K, Rb, Cs; M: CrIII, FeIII) are prepared by calcination and sintering of stoichiometric mixtures of Cr2O3, Fe2O3, alkali carbonates, and WO3 (800 °C, 12 h).